Are Postoperative Intravenous Antibiotics Indicated After Laparoscopic Appendicectomy for Simple Appendicitis? A Prospective Double-blinded Randomized Controlled Trial. Issue 2 (August 2020) - Mennie, Nicole; Panabokke, Gayathri; Chang, Annette; Tanny, Sharman Tan; Cheng, Wei; Pacilli, Maurizio; Ferguson, Peter; Nataraja, Ramesh M.
Abstract : Background: There is limited evidence for the use of postoperative antibiotics for simple appendicitis (SA) in children. Our aim was to conduct a prospective double-blinded randomized controlled trial to investigate this after a laparoscopic appendicectomy. Methods: Following ethical approval, children (⩽16 years) undergoing appendicectomy were recruited at a single institution. Patients were randomized intraoperatively to receive either 2 postoperative intravenous doses of placebo or antibiotics (Abx). All patients received a dose of Abx at induction of anesthesia. Primary outcome was the incidence of postoperative wound infection (WI), and secondary outcome was the incidence of intra-abdominal abscess formation. Data are reported as number of cases (%), median (range), relative risk, and analyzed using Mann Whitney U test, Chi-square test, as appropriate, a P -value ⩽0.05 was considered significant. Results: A total of 304 patients were randomized. Sixty-one were subsequently excluded due to protocol violations or recruitment errors; therefore, 243 were included in the final analysis. One hundred twenty-two patients received placebo and 121 Intravenous Abx. There was no difference between the sex (50F/72 M vs 47F/74 M, P = 0.8), median age (12.4 vs 12.2 years, P = 0.5), and postoperative length of stay in a hospital (27.2 vs 25.6 hours, P = 0.7). There was also no difference in the preoperative blood results. A total of 9 WIs occurred: 8/122 (6.6%) placebo versus 1/121 (0.8%) Abx, P = 0.01 [relative risk for WI 7.9 (95% confidence interval: 1.0–62.4)]. There were no intra-abdominal abscess in either groups. Conclusions: This prospective randomized double blinded randomized controlled trial has revealed a significant decrease in WI rates by giving 2 postoperative intravenous doses of Abx, suggesting postoperative Abx are of benefit in SA.